915 Maternal occupation is associated with maternal global dna (hydroxy) methylation in the second trimester of pregnancy. (24th April 2018) - Pauwels, S; Ghosh, M; Duca, RC; Huybrechts, I; Langie, SAS; Koppen, G; Devlieger, R; Godderis, L
Abstract : Introduction: Environmental factors, such as nutrition and occupational exposure can influence epigenetic marks like DNA methylation, which play a role in the development of chronic diseases. Methods: Data of the MAternal Nutrition and Offspring's Epigenome (MANOE) study was used to assess the effect of maternal occupation on maternal and infant DNA (hydroxy)methylation levels. Mothers were categorised in job categories according to the International Standard Classification of Occupations (ISCO). Maternal global DNA (hydroxy)methylation levels during each trimester of pregnancy and at delivery (n=122) was measured in whole blood via LC-MS/MS. Data were analysed with a one-Way ANOVA. Results: We found statistically significant differences in maternal global DNA methylation (p=0.008) and global DNA hydroxymethylation (p=0.004) at 20 weeks of pregnancy. Post hoc tests revealed that global DNA methylation and global DNA hydroxymethylation level was significantly lower when the mother had an intellectual/scientific/artistic profession (6.36% and 0.13%) as opposed to being a manager (7.77%, p=0.007% and 0.22%, p=0.002) or administrative staff (7.71%, p=0.003% and 0.2%, p=0.005). No significant differences between different working groups were found for global DNA (hydroxy)methylation in the first and third trimester of pregnancy and at delivery. Conclusion: The mother's occupation was associated with maternal global DNA (hydroxy)methylation levels only in the second trimester of pregnancy. The change in maternal global DNA (hydroxy)methylation in the second trimester of pregnancy could be due to hormonal changes during pregnancy, a shift in the one-carbon metabolism in the middle of pregnancy, but based on these results we also have to take into account maternal occupational exposure.